1989
DOI: 10.1148/radiology.171.2.2649926
|View full text |Cite
|
Sign up to set email alerts
|

Grade I hydronephrosis: pulsed Doppler US evaluation.

Abstract: This study was undertaken to determine whether the presence of blood vessels could mimic the appearance of grade I hydronephrosis on sonograms and thus cause false-positive readings. One hundred consecutive patients with grade I hydronephrosis were examined. Sample volumes were obtained with pulsed Doppler ultrasonography (US) at the site of the greatest separation of the central renal sinus echoes to determine if the separation was fluid accumulating in the collecting system, as in obstruction, or if the sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…One n o n o bstructed patient did have splitting of the central sinus complex that was evaluated with Doppler ultrasound and found to be a prominent renal vein. This is a simple yet very important procedure as it will eliminate many false positive diagnoses of hydronephrosis [9]. By eliminating the grade I hydronephrosis appearance due to blood vessels, grade I hydronephrosis can be properly emphasized as 7 of 17 patients with varying degrees of acute obstruction presented with grade I hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One n o n o bstructed patient did have splitting of the central sinus complex that was evaluated with Doppler ultrasound and found to be a prominent renal vein. This is a simple yet very important procedure as it will eliminate many false positive diagnoses of hydronephrosis [9]. By eliminating the grade I hydronephrosis appearance due to blood vessels, grade I hydronephrosis can be properly emphasized as 7 of 17 patients with varying degrees of acute obstruction presented with grade I hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Even when hydronephrosis was detected in a clinical setting suspicious for obstruction, misdiagnosis was possible. Not all hydronephrotic kidneys are obstructed and central renal sinus splitting may be due to vascular causes [7][8][9]. Because of these limitations of ultrasound, the intravenous urogram (IVU) has remained the mainstay of diagnosis in the setting of acute colicy obstruction.…”
mentioning
confidence: 99%
“…In contrast, blood vessels account for the sonolucent hilar region in up to 40% of adults and 61 % of children that appear to have mild pelviectasis by real-time ultrasound alone. 9 This difference between fetal and adult kidneys may relate to the high prevalence of normal pelviectasis in the fetus. The etiology of so-called •physiologic• pelviectasis in the fetus has not been established, but it has been postulated that it may relate to increased urine production late in pregnancy, relaxation of collecting system smooth muscle by maternal hormones, and/or vesicoureteral reflux.u · 6 • 10-12 Additionally, the current study did not include fetal kidneys with sonolucent regions less than 2 mm in AP dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Its use is limited if there is no pyelocaliectasis, and it cannot differentiate between obstructive and nonobstructive dilatation of the renal collecting system. 5,7,[10][11][12][13][14] Studies have shown that 2 hours after onset of a renal obstruction, renal vascular resistance (RVR) increases and renal blood flow (RBF) decreases. [15][16][17][18] Doppler sonography can provide information about these hemodynamic changes.…”
mentioning
confidence: 99%
“…When the central echo complex was separated minimally by distended anechoic calyceal structures, the kidneys were classified as hydronephrotic (grade 1) 11,14 ; otherwise, they were categorized as nondilated.…”
mentioning
confidence: 99%